Vulnerability Analysis of CSP Based on Stochastic Game Theory - Jiajun Shen; Dongqin Feng (Journal of Control Science and Engineering)
With the development of industrial informatization, the industrial control network has gradually become much accessible for attackers. A series of vulnerabilities will therefore be exposed, especially the vulnerability of exclusive industrial communication protocols (ICPs), which has not yet been attached with enough emphasis. In this paper, stochastic game theory is applied on the vulnerability analysis of clock synchronization protocol (CSP), one of the pivotal ICPs. The stochastic game model is built strictly according to the protocol with both Man-in-the-Middle (MIM) attack and dependability failures being taken into account. The situation of multiple attack routes is considered for depicting the practical attack scenarios, and the introduction of time aspect characterizes the success probabilities of attackers actions. The vulnerability analysis is then realized through determining the optimal strategies of attacker under different states of system, respectively.